ANALISIS PERBANDINGAN KEPUTUSAN PEMBELIAN COMPLEX BUYING BEHAVIOUR PADA KONSUMEN PERUMAHAN SARI RESIDENCE - Nusun Ulina; Jushermi '; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was held at PT. Hutama Property Pekanbaru to find out the comparison of customer purchasing decision toward location, price, design, quality, and facility. the population on this research was customer's Sari Residence and Wijaya Kusuma in Pekanbaru that bought the unit.Keywords: location, price, design, quality, facility.